THE SOCIALIZATION ABOUT THE RIMBANG FRUIT ACTIVITY TEST (SOLANUM TORVUM SWARTZ) AS AN IMMUNOSTIMULATOR: SOCIALIZATION ABOUT THE RIMBANG FRUIT ACTIVITY TEST (SOLANUM TORVUM SWARTZ) AS AN IMMUNOSTIMULATOR - Marbun, Romauli Anna Teresia; Br Situmorang, Novidawati; Wahyuni, Siti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2022)
Decreased immune system function can occur when the invasion of foreign substances cannot be balanced by immune cells. So, we need substances or materials that can improve the immune system and increase its regulation. Rimbang fruit (Solanum torvum Swartz) is a native vegetable that has been consumed by local people for a long time. Previous research stated that rimbang fruit is rich in phenolic compounds, namely flavonoid derivatives, namely flavonols (quercetin, kaempferol, and myricetin) and flavones (apigenin and luteolin). These secondary metabolites indicate that rimbang fruit has the potential to regulate the regulation of the immune system supported by its high antioxidant power. The research method used experimental methods, extraction method with 96% ethanol solvent maceration method. Variations in the dose of rimbang fruit extract used were doses of 50%, 100%, 200%, and 400%. The positive control used was Levamisole. The negative control used was CMC-Na 0.5%. The immunomodulator test method uses the antibody titer method using male rats as test animals. Immunogens used sheep red blood cells. Information provided to pharmacy students. From this it was concluded that the rimbang fruit extract had an immunostimulating effect at an optimal dose of 400 mg/kg body weight. These findings are shared with students and the public through Zoom meetings to help them understand the benefits of rimbang as an immunostimulator.